Factors related to sustainable employment of people with acquired brain injury or spinal cord injury: The employer's perspective - Schiffmann, Barbara; Finger, Monika E.; Karcz, Katarzyna; Staubli, Stefan; Trezzini, Bruno (Frontiers in Rehabilitation Sciences, 2022)
Background: Of those people with an acquired brain injury (ABI) or spinal cord injury (SCI) who initially successfully returned to paid employment, some drop out of the workforce before they reach official retirement age. Employers play a central role in ensuring a sustainable work situation for employees with a disability and preventing such drop-outs. However, little research has been done on factors and mechanisms that play a role in this from the employer's perspective. Purpose: The purpose of this study was to determine factors which, from employer's perspective, have a particularly positive or negative influence on sustainable employment of people with ABI or SCI. Methods: Twenty semi-structured interviews were conducted with employers of people with ABI or SCI and thematically analyzed. Results: The identified influencing factors could be assigned to four thematic areas for both health conditions: socio-demographic and psychological characteristics of the disabled person, their work performance, the work environment, and other social/environmental conditions. More specifically, good self-management of the disability by the person concerned, combined with proactive communication of needs, is an important prerequisite for long-term employment. Discrepancies in job performance expectations and evaluations between employees and employers pose a challenge. Employers feel responsible for providing an optimal working environment so that the employee with a disability can develop his or her full potential. This includes suitable work tasks, opportunities for development, a sensitive work team, flexible work organization, provision of resources to address specific needs and an inclusive corporate culture. Employers find the support provided by specialists during occupational integration very helpful, as they often lack the knowledge to design the working environment in accordance with the person's needs. Conclusions: Aspects that are critical for both person with ABI or SCI's sustainable employment, are addressed in vocational rehabilitation with support of professionals. Such support is often lacking when changes and problems arise in the further course of an affected person’s employment that may lead to a drop-out. Therefore, the self-efficacy of those affected, the ongoing sensitization of the environment and the expansion of low-threshold health-specific support services in the event of problems are of great importance.